Anthropometric and physiological characteristics of young soccer players according to their playing positions: Relevance for competition success - Lago-Penas, C.; Casais, L.; Dellal, A.; Rey, E.; Dominguez, E. (The Journal of Strength and Conditioning Research, 2011)
The aim of this study was to establish the anthropometric and physiological profiles of young soccer players according to their playing position and to determine their relevance for competition success. Three hundred and twenty-one young male soccer players participated in the study. Players, age 15.63 (±1.82) years, range 12-19 years, were classified into the following groups: Goalkeepers (n = 35), Central Defenders (n = 53), External Defenders (n = 54), Central Midfielders (n = 61), External Midfielders (n = 46), and Forwards (n = 72). The anthropometric variables of participants (height, weight, body mass index, 6 skinfolds, 4 diameters, and 3 perimeters) were measured. Also, their somatotype and body composition (weights and percentages of fat, bone, and muscle) were calculated. Participants performed the 20-m progressive run test to estimate their relative VO2max, a sprint test (30 m flat), and 3 jump tests (squat jump, countermovement jump, and Abalakov test). External Midfielders were the leanest and shortest. In contrast, Central Defenders and Goalkeepers were found to be the tallest and heaviest players. They also had the largest fat skinfolds. In general, the results show that heavier and taller young soccer players performed better in vertical jumps and 30-m sprint, whereas leaner players performed better in the 20-m progressive run test. Players were classified into 2 groups according to the final ranking of their teams at the end of the season. Players from successful teams performed slightly better than players from unsuccessful teams in the physiological test, but these differences were not statistically significant. Moreover, players from successful teams were found to be leaner and more muscular than their unsuccessful counterparts.